Convergent and divergent two-dimensional coordination networks formed through substrate-activated or quenched alkynyl ligation - Čechal, Jan; Kley, Charistopher S.; Kumagai, Takashi; Schramm, Frank; Ruben, Mario; Stepanow, Sebastian; Kern, Klaus (Royal Society of Chemistry, 2014)
Metal coordination assemblies of the symmetric bi-functional 4,4-di-(1,4-buta-1,3-diynyl)-benzoic acid are investigated by scanning tunnelling microscopy on metal surfaces. The formation of long-range ordered, short-range disordered and random phases depends on the competition between the convergent and divergent coordination motifs of the individual functional groups and is crucially influenced by the substrate.

Metal coordination assemblies of the symmetric bi-functional 4,4-di-(1,4-buta-1,3-diynyl)-benzoic acid are investigated by scanning tunnelling microscopy on metal surfaces. The formation of long-range ordered, short-range disordered and random phases depends on the competition between the convergent and divergent coordination motifs of the individual functional groups and is crucially influenced by the substrate.
Convergent and divergent two-dimensional coordination networks formed through substrate-activated or quenched alkynyl ligation
Keywords: Metal-organic coordination networks; self-assembly; surfaces; Metal-organic coordination networks; self-assembly; surfaces